HUBUNGAN PENGAWASAN KEPALA SEKOLAH DENGAN DISIPLIN KERJA GURU DALAM MENGAJAR DI SMK NEGERI 2 BUKITTINGGI - Affan Affan Fattria N (Jurnal Bahana Manajemen Pendidikan, 2014)
This research in background overshadow from result of perception of writer in SMK Country 2 Town of Bukittinggi showing activity discipline learn still lower in teaching. This matter is anticipated related to observation of headmaster, because executed observation not yet optimal will have an effect on to the teacher activity discipline in teaching. This research purpose to see observation relation to activity discipline learn in teaching. Its population of teacher which is amount 70 and people of sample 40 one who is taken with technique of Proportional Stratified Random Sampling. this Instrument Research is kuesioner which in form of scale of Likert which have in validity test and of reliable. To test hypothesis use formula of Product Moment, test-R and of test-T, while r² used to see the level of observation of headmaster to activity discipline learn in teaching. Result of this research is observation of good headmaster and activity discipline learn in teaching have good enough and there are relation meaning between observation of headmaster with activity discipline learn in teaching in SMK Country 2 Bukittinggi at trust level 95 Kata kunci: pengawasan dan disiplin kerja dalam mengajar